Co-assembly of Zn(SPh)2 and organic linkers into helical and zig-zag polymer chains - Blair, Richard G. (2013)
Two novel one-dimensional coordination polymers, single helicate [Zn(SPh)2(TPyTA)(EG)]n (EG=ethylene glycol) (1) and zig-zag structure [Zn(SPh)2(BPyVB)]n (2), were synthesized under solvothermal conditions at 150 °C or room temperature by the co-assembly of Zn(SPh)2 and organic linkers such as 2,4,6-tri(4-pyridyl)-1,3,5-triazine (TPyTA) and 1,3-bis(trans-4-pyridylvinyl)benzene (BPyVB). X-ray crystallography study reveals that both polymers 1 and 2 crystallize in space group P21/c of the monoclinic system. The solid-state UV–vis absorption spectra show that 1 and 2 have maxium absorption onsets at 400 nm and 420 nm, respectively. TGA analysis indicates that 1 and 2 are stable up to 110 °C and 210 °C.